The outer membrane protein Amuc_1100 of Akkermansia muciniphila promotes intestinal 5-HT biosynthesis and extracellular availability through TLR2 signalling. Issue 8 (30th March 2021) - Wang, Junchao; Xu, Wenjuan; Wang, Rongjuan; Cheng, Rongrong; Tang, Zhengquan; Zhang, Min
Abstract : The outer membrane protein Amuc_1100 of A. muciniphila promotes intestinal 5-HT biosynthesis and extracellular availability through TLR2 signalling. Conversely, 5-HT will in turn to affect the composition of microorganisms in the gut. Abstract : Akkermansia muciniphila is a probiotic inhabiting host intestinal mucus layers and displays evident easing or therapeutic effects on host enteritis and metabolic disorders such as obesity and diabetes. The outer membrane protein Amuc_1100 of A. muciniphila is likely to play a crucial role during the interaction with the host. 5-HT is a neurotransmitter and a key signal molecule regulating the gastrointestinal tract functions and other organs, which is involved in diverse physiological and pathological processes. This study demonstrated that Amuc_1100 could promote the expression of the 5-HT synthesis rate-limiting enzyme Tph1 in RIN-14B cells and reduce the expression of the serotonin reuptake transporter (SERT) in Caco-2 cells through direct interaction with TLR2, thereby improving 5-HT biosynthesis and extracellular availability. Using antibiotic-treated mice as animal models, we found that after gavage with A. muciniphila or Amuc_1100, Tph1 expression increased and SERT expression decreased in colon tissues. The 5-HT concentrations in colon tissues and blood were markedly elevated simultaneously. We also found that A. muciniphila or Amuc_1100 improved the gastrointestinal motility function and restored gut microbiota abundance and species diversity in antibiotic-treated mice. These results suggest that A. muciniphila can regulate the host intestinal 5-HT system via its outer membrane protein Amuc_1100 and TLR2. This mechanism represented an important approach through which A. muciniphila interacts with the host and further influences 5-HT-related physiological functions. These results advance the understanding of interplay mechanisms between the gut microbiota and the host, which could be the basis for new intervention strategies for related diseases.